Low Serum Irisin as A Risk Factor of Sarcopenia in Elderly - Aryana, I Gust Putu Suka; Putrawan, I.B.; Purnami, Ni Ketut Rai; Kuswardhani, R.A. Tuty; Astika, I Nyoman; Suastika, Ketut; Adiatmika, I Putu Gede; Jawi, I Made; Wande, I Nyoman (UI Scholars Hub, 2020)
Introduction. Sarcopenia is a condition characterized by a decrease in muscle mass accompanied by a decrease in strength and/or function. Sarcopenia is closely related to the aging process, but the mechanism of its occurrence is still not fully understood. Skeletal muscle is the largest organ in the human body, so the myokine produced through muscle contraction opens a new paradigm regarding the central role of muscles in regulating metabolism and other organ functions. One of the myokines that are currently found to affect physical activity is Irisin. This study aims to determine the role of low Irisin levels in serum as a risk factor for sarcopenia in the elderly. Methods. This case-control study was conducted in Denpasar City from January 2020 to October 2020. The sample was selected using purposive consecutive sampling with matching age and gender, with 54 subjects, 27 case groups, and 27 control groups aged ≥60 years. Sarcopenia status is enforced by the criteria of the Asian Working Group for Sarcopenia (AWGS). Irisin serum levels were measured by enzyme-linked immunosorbent assay (ELISA). Results. Based on 54 subjects, the mean age in cases was 69.79 (SD 5.00) years and controls 67.89 (SD 4.50) years (p = 0.152), the proportion of male:female both in cases and controls group was 9:18. The cut-off point value wass based on the irisin ROC curve 4.51 ng/L. Nutritional status (OR = 3.40 (95% CI = 1.11 - 10.40); p = 0.029) and irisin (OR = 25.30 (95% CI = 6,00 - 106.66); p = <0.001) had an effect on sarcopenia. Factors that purely influence sarcopenia were found in low irisin (OR = 103.41 (95% CI = 7.83 – 1,364.99; p = <0.001). Conclusions. Low Irisin level is a risk factor for sarcopenia in the elderly. Irisin could be considered for further investigation in an effort to become a target for both preventive and curative therapy for sarcopenia.